COGNITIVE FACTORS IN LANGUAGE LEARNING: TRANSFER, INTERFERENCE, OVERGENERALIZATION - Turaeva, Shoira (Журнал иностранных языков и лингвистики, 2021)
There is an increasing interest in language learning today, but there are also barriers to language learning. The process of learning a language is regarded as one of the most contentious issues in our modern society. The authors attempted to examine the main characteristics of cognitive factors using the examples of transfer, interference, and overgeneralization and discussed the difficulties in learning languages, how to overcome them, easy mastery of languages, and indeed the unifying and distinguishing aspects of learning two or three languages. The similarities and differences, as well as the significance of transfer in language learning, are thoroughly discussed. This paper focuses on the article’s strong and weak points, as well as its language.